World Bank Filming at Nyando - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
On 21 - 22 March 2014, CCAFS East Africa hosted World Bank film crew at the Nyando Climate Smart Villages. We visited John Obuom's Climate-Smart Farm. He is one of the champion farmers in the region. Photos V.Atakos (CCAFS)